2015
DOI: 10.4103/2229-5178.164478
|View full text |Cite
|
Sign up to set email alerts
|

Atrichia congenita

Abstract: Atrichia congenita is a rare genodermatoses is characterized by a mutation of the human hairless (HR) gene on chromosome 8p22. There is loss of scalp hair between one to six months of age, after which no growth occurs. Eyebrow, eyelash, and body hair may also be sparse or absent; patients may have a few pubic and axillary hairs. The condition may present in isolation or along with other defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Atrichia congenita with papular lesions is a rare, autosomal recessive form of total alopecia of the scalp, eyebrows, eyelashes, axillary and pubic hair, characterized by hair loss soon after birth and the development of keratin-filled cysts or horny papules over extensive areas of the body involving face, neck, limbs, and trunk. 1,2 This condition was noted among the Irish Traveler gypsies. Ahmad et al first referred to this condition as congenital atrichia.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Atrichia congenita with papular lesions is a rare, autosomal recessive form of total alopecia of the scalp, eyebrows, eyelashes, axillary and pubic hair, characterized by hair loss soon after birth and the development of keratin-filled cysts or horny papules over extensive areas of the body involving face, neck, limbs, and trunk. 1,2 This condition was noted among the Irish Traveler gypsies. Ahmad et al first referred to this condition as congenital atrichia.…”
Section: Discussionmentioning
confidence: 96%
“…1 Atrichia congenita with papular lesions (APL) represents a heterogeneous group of genodermatoses characterized by irreversible complete hair loss soon after birth which is associated with the development of keratin-filled cysts over the body. 2,3 The condition may occur in isolation in both sporadic and familial forms or along with other defects In the isolated familial form, inheritance is usually autosomal recessive, although autosomal dominant inheritance has occurred in some families. 1,2 The gene locus for familial cases is on chromosome 8p21-22 (ALUNC-alopecia universalis congenitalis) and mutation of the human hairless (HR) gene has been proposed in atrichia congenital.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies also concluded that ballistic charge transport along the direction of 1-D crystals should be much more effective than diffusive transport in the powdered materials. [8,11,13,32] Additionally, the UV-visible light photocatalytic activity of the tube-shape photocatalyst was further measured by varying the operating parameters, which was found to be closely dependent on the catalyst dosage (Figure 9). For a reasonable assessment of these two morphologies of MOF and factual potential for photocatalytic application, commercial TiO 2 (Degussa P-25) was taken as a benchmark photocatalyst.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
“…[10] MOFs with a rod/needle-like structures can be used as photocatalysts for the removal of organic pollutants. [11][12][13] Mahata et al (2006) were the leading researchers who investigated the efficiency of MOFs as photocatalysts for removing organic pollutant from water. [14] Subsequently, the researchers have discovered many MOFs that can act as photocatalyst under the exposure of UV-visible light, due to the LMCT states.…”
Section: Introductionmentioning
confidence: 99%